Evaluation of antimalaria activity and acute toxicity of Xetospongia sp - Abdillah, Syamsudin; Noor, Noriah Mohd; Ahmad, Rahmatul Wahidah; Parama Cita, Yatnita (Science Publications, 2013)
We investigated the in vivo activity of extract of Xetospongia sp against Plasmodium berghei Strain ANKA and acute toxicity in mice. The ethanolic extracts of the Xetospongia sp (50-400 mg kg-1 day) were screened for blood schizonticidal against P. berghei strain ANKA in mice during early and established infections. Acute toxicity of extracts of Xetospongia sp at the dose 5000 mg kg-1 on mice administeredorally exhibited no toxicity, as evident in that fact that no histopathological changes were observed in some essential organs, such as liver, heart, digestive tract and kidney. The ethanolic extracts (50-400 mg kg day-1) exhibited a significant antimalarial activity both in the 4-day early infection test and in the established infection and they were found to be relatively safe up to a dosage of 5000 mg kg-1, with an LD50 value of >500 mg kg-1.